Formulation And In Vivo Evaluation Of Once A Day Push-Pull Osmotic Tablet - RAJESHRI WAKODE; AMRITA BAJAJ (International Journal of Pharma and Bio Sciences, 2010)
Once a day push pull osmotic tablets containing pramipexole as an antiparkinson’s agent were developed and evaluated for in vivo efficacy. Push pull osmotic tablets are bilayered tablets consisting of pull layer (drug layer) and push layer (polymer layer) coated with semipermeable cellulose acetate membrane containing water leaching pore forming agents. To determine the in vivo efficacy of formulation, symptoms of Parkinson’s disease were induced in male Wistar rats using reserpine 5mg/kg, (i.p) and induction of disease was confirmed with the help of in vivo tests. Striatal dopamine content was decreased from 12 ng/gm of tissue in normal control to 0.6 ng/gm in disease induced rats. Dopamine content was found to increase to 6ng/gm after intragastric administration of push pull osmotic tablet and even the motility in rats was improved. Various pharmacokinetic parameters were estimated and the studies revealed that the developed formulation maintained plasma levels of pramipexole for a period of 24 hrs.